Obreiros pacíficos: o Círculo de Operários e Trabalhadores Católicos São José (Fortaleza, 1915 - 1931) - Lima, Ana Cristina Pereira (2009)
We analyze the performance of the Círculo de Operários e Trabalhadores Católicos São José, in Fortaleza (CE) from 1915 to 1931. It was considered aspects of worker associations, the reach of the Catholic Church and the heterogeneity of worker class in the city. Thus, we decided to study the various experiences of workers in this period, which involves association possibilities, rights, education, leisure, usage and routes within the city. We understood the Círculo Operário as a collective subject effectively participating in the workers’ association of Fortaleza during the First Republic.